Improving Reading Accuracy of ACS712 Current Sensor with ATmega328 10-Bit ADC: Enhancing Resolution to 5Ma/BIT via AD620 Differential Amplifier and Kalman Filters - Pardede, Josefan Osbert; Brahmana, Kurnia (Talenta Publisher, 2023)
The study focuses on the development of a current measuring device that incorporates the ACS712 current sensor, enhances the reading sensitivity of the ACS712 current sensor from 27mA/bit to 5mA/bit through the implementation of an AD620 differential amplifier, and employs a Kalman filter for improved accuracy. This increase in current uses a differential amplifier AD620. An increase in the sensitivity of the reading is carried out by utilizing the initial value of the ACS712 sensor when it has not been connected to the circuit or an offset of 512 to 0 so that 10bit ADC data can be utilized to measure 4880 mV/A so that the accuracy of reading 1-bit data is equal to 4, 8 mV/mA after being given a gain of 26.5 times. The signal enhanced from the AD620 will be filtered using the Kalman filter program so that the signal generated after the increase will be stable, and the current value that has been read will be displayed on the LCD screen. Based on the analysis results, the ACS712 current sensor can effectively measure up to 5mA/bit stably using the AD620 differential amplifier and Kalman filter.